2019
DOI: 10.1002/jmv.25533
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of liver‐related disease in patients with chronic hepatitis C virus infection: An analysis using a Markov chain model

Abstract: Background Long‐term prognosis of patients with chronic hepatitis C infection (HCV) remains incompletely characterized. We investigated the long‐term prognosis of liver disease in patients with chronic HCV infection who have not received antiviral therapy. Methods A total of 2304 patients with chronic HCV who were not received interferon‐based therapy were included. Results In the assessment of 1‐year disease state of liver transition probabilities, progression to chronic hepatitis occurred in 12% to 14% of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(91 reference statements)
1
11
0
Order By: Relevance
“…Hepatitis C virus (HCV) infection affects an estimated 1.8 million people globally and is the leading cause of hepatocellular carcinoma (HCC) [ 1 ]. Reports have indicated that the most serious outcome of HCV infection is hepatocarcinogenesis or progressive hepatic failure resulting in death [ 2 ], and that HCV infection increases the rate of complications associated with extrahepatic morbidity, which accounted for about 50% of the HCV deaths [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection affects an estimated 1.8 million people globally and is the leading cause of hepatocellular carcinoma (HCC) [ 1 ]. Reports have indicated that the most serious outcome of HCV infection is hepatocarcinogenesis or progressive hepatic failure resulting in death [ 2 ], and that HCV infection increases the rate of complications associated with extrahepatic morbidity, which accounted for about 50% of the HCV deaths [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we simulated the per cent probabilities of transition across liver states over the long term in patients with chronic hepatitis or cirrhosis at age 40 and 60, stratified by sex and HCV eradication status. Although we did not perform a validation analysis in this study, we have extensively studied 42‐47 long‐term prognosis in patients with chronic hepatitis B virus and HCV infection in other several cohorts using Markov chain model simulation. Therefore, we strongly believe that Markov chain models are accurate and useful for simulating the prognosis of chronic hepatitis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Markov model is a useful method to describe the process of individuals passing through a series of states in continuous time. These types of patterns explain how patients transition between long-term disease states, which is popular in explaining the natural history of disease [38,39]. Moreover, the Markov model has another advantage that it can utilize data with limitation in quality and accuracy, which may be collected retrospectively [40].…”
Section: Discussionmentioning
confidence: 99%